Just for december ebook - Williams, Laura Jane (2022)
Evie Bird is a romance writer whose latest bestseller is being made into a Christmas movie. Duke Carlisle is a world-famous actor who has landed the role of leading man. When Evie and Duke meet on set, it's a frosty encounter – even icier than the cobbled Bavarian streets they're filming on. But after images of them arguing leak to the press and put the movie in jeopardy, they are left with no choice but to fake date until the cameras stop rolling. As the pair start to put their differences aside, their feelings gradually begin to thaw... But can sparks ever really fly in a snowstorm? Laura Jane Williams is BACK with the most romantic read of the festive season. If you love Christmas movies like The Holiday and The Christmas Prince, this is the read to warm your heart with this December. Readers love Just for December: 'This book has all the elements of a fun romcom that I love. It is dual pov, has great characters who love books and movies, and is enemies-to-lovers and fake dating. What more could you ask for?' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'Such a sweet Christmas story...Loved the characters! Five stars.' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'A five-star read that you need for more than just December! Evie Bird just made me swoon...I felt her in my bones. A must-have Christmas read.' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'A rom com with a difference...There was so much to love about this book! I absolutely adored the movie magic at Christmas setting...An enjoyable festive Hollywood romance that I'd recommend.' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'A must-read book!...I simply fell in love with Laura's writing style. I loved the chemistry between the characters.' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'Where do I start? I LOVED THIS BOOK! My favourite out of all the books Laura has written so far!' NetGalley Reviewer, ⭐⭐⭐⭐⭐ 'A lovely story.' NetGalley Reviewer, ⭐⭐⭐⭐⭐